Janice VanCleave's astronomy for every kid : 101 easy experiments that really work - VanCleave, Janice Pratt (New York : Wiley, 1991)
Presents a collection of 101 astronmy experiments, for elementary students, and includes information and ideas for science fair projects. Includes illustrations.
Includes index.
6.5
6.5
5-8.
5-8
Keywords: Astronomy -- Experiments -- Juvenile literature; Astronomy -- Experiments; Science -- Experiments; Astronomy -- Experiments; Science -- Experiments